Host plant specificity in the infection of C3 and C4 plants by Azospirillum spp - Baldani, J. I.; Pereira, P. A.A.; Rocha, R. E.M da; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
The occurence of Azospirillum brasilense and A. lipoferum and their nir+ and nir- variants was determined in soil and in non-sterilized and sterilized roots of the C3 cereals wheat, rye, barley and oat and of several C4 grasses. The C3 cereals were planted in pots with red-yellow podzolic soil and examined at two growth stages. The C4 forage grasses were collected in fields where the respective species were predominant. In all soils A. brasilense seemed to predominate. The proportion of A. brasilense nir- was above 80% in all C3 cereals when surface sterilized roots were examined. Azospirillum isolates from surface sterilized roots of C4 grasses were predominantly A. lipoferum but only in some species (Panicum maximum, Sorghum vulgare and Brachiaria sp) the nir- forms predominated. A weed belonging to Cyperaceae (Cyperus rotundus) was also infected by A. lipoferum nir- as in the case of other C4 grasses. The only exception among the C4 Gramineae was sugar cane which seemed to behave like the C3 cereals, and all 24 isolates from surface sterilized roots were A. brasilense nir-.